FACTORS ASSOCIATED WITH HOUSING SAFETY AMONG ELDERLY PEOPLE IN UBON RATCHATHANI PROVINCE - Yokphonchanachai, Chaiyakrit; Paengprakhon, Yanitha; Duangsri, Jaruporn; Chada , Wilawan; Sukontajit, Penmas (Life Sciences and Environment Journal, 2025)
This descriptive cross-sectional study aimed to investigate the factors associated with residential safety among elderly people in Ubon Ratchathani Province. The sample consisted of 34 elderly individuals selected using Multistage Sampling. A structured questionnaire was used to assess knowledge, attitudes, and self-protective behaviors related to residential safety. Data were analyzed using descriptive statistics, Pearson’s Chi-square test, and Pearson’s correlation. The results indicated that most participants were female (88.2%) with a mean age of 74.6 years. The majority demonstrated low levels of safety knowledge (64.7%), while their attitudes and protective behaviors were at a moderate level (58.8% and 82.4%, respectively). Significant factors associated with self-protective behavior included cohabitation (p = 0.050) and past residential injuries (p = 0.049). Knowledge showed a significant correlation with protective behavior (p ≤ 0.05), but not with attitudes (p >0.05). Conclusion: The findings emphasize the need to enhance knowledge and improve residential environments to effectively promote safety behaviors among the elderly in a sustainable manner.